NEURODEVELOPMENTAL DISORDERS IN CHILDREN WITH EPILEPSY: INTELLECTUAL DISABILITY AND AUTISM SPECTRUM DISORDERS - N. N. Zavadenko (Эпилепсия и пароксизмальные состояния)
The majority of epilepsy cases have their onset in childhood. Compared to their peers, many more children with epilepsy suffer from severe neurodevelopmental disorders, including intellectual disability and autism spectrum disorders. In the present report, the incidence of intellectual disability and autism spectrum disorders among children with epilepsy is reviewed. Four types of connection between epilepsy and autism are discussed: these two conditions are independent as they have different etiologies and may co-occur just by chance; epilepsy and autism are associated because both originate from the same genetic defect or from an early CNS damage; autism is caused by the epileptic process, which interferes with the developing brain networks involved in communication and social behavior. Studies demonstrating positive effects of levetiracetam on the behavioral and cognitive functions (memory, attention) in epileptic children are cited.